The effect of timing of initiation of renal replacement therapy on mortality: A retrospective case–control study. (February 2021) - Engoren, Milo; Maile, Michael D; Heung, Michael; Blum, James M; Blank, Ross; Napolitano, Lena M; Park, Pauline K; Raghavendran, Krishnan; Jewell, Elizabeth S; Meldrum, Craig
Purpose: To determine if earlier initiation of renal replacement therapy (RRT) is associated with improved survival in patients with severe acute kidney injury. Methods: We performed a retrospective case–control study of propensity-matched groups with multivariable logistic regression using Akaike Information Criteria to adjust for non-matched variables in a surgical ICU in a tertiary care hospital. Results: We matched 169 of 205 (82%) patients with new initiation of RRT (EARLY group) to 169 similar patients who did not initiate RRT on that day (DEFERRED group). Eighteen (11%) of DEFERRED eventually received RRT before discharge. By univariate analysis, ICU mortality was higher in EARLY (n = 60 (36%) vs. n = 23 (14%), p  < 0.001) as was hospital mortality (n = 73 (43%) vs. n = 44 (26%), p  = 0.001). Of the 18 RRT patients in DEFERRED, 12 (67%) died in ICU and 13 (72%) in hospital. After propensity matching and logistic regression, we found that EARLY initiation of RRT was associated with a more than doubling of ICU mortality (aOR = 2.310, 95% confidence interval = 1.254–4.257, p  = 0.007). However, after similar adjustment, there was no difference in hospital mortality (aOR = 1.283, 95% CI = 0.753–2.186, p  = 0.360). Conclusions: While ICU mortality was increased in the EARLY group, there was no difference in hospital mortality between EARLY and DEFERRED groups.